Disease burden attributable to endocrine-disrupting chemicals exposure in China: A case study of phthalates - Yan Cao; Li Li; Kaihui Shen; Jianguo Liu* (Science of the Total Environment, 2019)
While it has been acknowledged that exposure to endocrine-disrupting chemicals (EDCs) is associated with human diseases, the overall disease burden attributable to the exposure to a specific EDC has rarely been evaluated. Based on existing models for assessing probabilities of causation and a comprehensive review of available data, we analyzed the burden of three diseases, i.e., male infertility, adult obesity, and diabetes, among the general Chinese population resulting from exposure to phthalates. Our estimation indicates that exposure to phthalates is associated with ~2.50 million cases of the three diseases across China in 2010, causing ~57.2 billion Chinese Yuan (equivalent to ~9 billion US dollars) of health care costs in a year. Male infertility has the largest number of cases, followed by adult obesity and diabetes. Based on these phthalate-specific estimates, we further estimated that the total disease cost due to exposure to the overall EDCs amounted to ~429.43 billion Chinese Yuan in China in 2010, accounting for 1.07% of nationwide gross domestic product (GDP). When comparing our results with an earlier estimate for the European Union (EU) member countries, we find that exposure to phthalates leads to quite a similar disease burden per unit of GDP in both regions. Our study illustrates the considerable socio-economic impact of EDC exposure on human society, implying the imperative need for global risk reduction actions on EDCs, especially in view of the 2030 Sustainable Development Goals.